The Factors That Inhibit The Achievement Of The Indonesian Correctional Institutions’ Objectives - sulistya eviningrum (Law and Justice, 2022)
Introduction: The role of rehabilitating and developing prisoners is stipulated in Law No. 12 of 1995 on Correctional Institutions. The development of prisoners is still ineffective in some aspects. This study analyzes the factors that inhibit the achievement of the Indonesian criminal institutions’ objectives. Methods: This is juridical normative legal research that was conducted with a statute approach to analyze all laws concerning the discussed legal issues. Results and Discussion: The results show that several factors inhibit the achievement of the Indonesian correctional institutions’ objectives, namely: (1) The legal factor: There is a lack of regulation on the third parties’ participation in rehabilitating prisoners at correctional institutions; (2) The law enforcement factor: Correctional institution officers do not specially guide inmates to increase their skills, as they only maintain security and order; (3) The facility factor: There is a lack of adequate facilities in correctional institutions; (4) The society factor: There is a lack of social participation in rehabilitating prisoners due to their lack of concern for prisoners; (5) The cultural factor: There is still a negative stigma that is associated with ex-convicts. Thus, many of them face difficulties in reintegrating into society. Conclusion: The factors of law; law enforcement; facilities; society; and culture affect the achievement of the correctional institutions' objectives. These factors correlate as they are the essence of the success in rehabilitating inmates.